An Expert System for Diagnosing Laptop Hardware Failures Using a Web-Based Certainty Factor Method - Tarigan, Mhd Hidayat Fajri; Martiano, Martiano (Jurnal ICT : Information and Communication Technologies, 2026)
Rapid technological developments are driving the increased use of laptops in various activities, which indirectly increases the potential for hardware damage. In laptop repair services, the damage identification process generally relies on the technician's experience, resulting in subjective and potentially inconsistent decisions. This situation demonstrates the need for a system capable of providing structured and measurable diagnostic support. The approach used is the Certainty Factor method to represent the level of confidence in diagnostic results. The developed web-based expert system allows users to identify damage based on selected symptoms, then produces output in the form of the type of damage along with a confidence value as a percentage. Evaluation is carried out by comparing the system's diagnostic results with those of experts in a number of test cases. The test results show a good level of agreement, so the system can be used as an aid in the initial diagnosis of laptop hardware damage.